ANALYSIS OF WIDAL SLIDE TEST ON TIFOID FEVER PATIENTS IN SUNDARI MEDAN GENERAL HOSPITAL - Tiara Rajagukguk (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
Typhoid fever is an acute systemic disease caused by Salmonella typhi and Salmonella paratyphi A, B and C are characterized by prolonged fever, bacteremia without changes in the endothelial system. Salmonella is a genus of gram-negative enterobacteria bacteria in the form of rods, flagellated, without spores, capsules, and anaerobes that cause typhoid and paratyphoid. Salmonella is the leading cause of foodborne illness. In general, Salmonella causes diseases of the digestive organs. Salmonella antigen structure consists of flagellar antigen (H antigen), somatic antigen (O antigen). Widal test is a serological test procedure to detect Salmonella typhi bacteria infection that causes typhoid fever. This test will show the Salmonella antibody reaction to O- somatic, H-flagellar and Vi (bacterial hoops) antigens in the blood. Culture is the gold standard in examining typhoid fever cases to date because in culture we can determine the morphology of Salmonella. This type of research is a descriptive study that aims to analyze the results of the Widal Slide Test with the agglutination method in the Sundari General Hospital Laboratory, Medan. Of the 15 samples analyzed, the results of the Widal Slide Test were obtained for 33% of typhoid fever patients with agglutination and 67% of those without agglutination. The results were Salmonella typhi O = 4 samples, Salmonella typhi H = 1 sample, Salmonella paratyphi AO = 1 sample, Salmonella paratyphi BO = 2 samples, and Salmonella paratyphi CO = 3 samples. This type of research is a descriptive study that aims to analyze the results of the Widal Slide Test with the agglutination method in the Sundari General Hospital Laboratory, Medan. Of the 15 samples analyzed, the results of the Widal Slide Test were obtained for 33% of typhoid fever patients with agglutination and 67% of those without agglutination. The results were Salmonella typhi O = 4 samples, Salmonella typhi H = 1 sample, Salmonella paratyphi AO = 1 sample, Salmonella paratyphi BO = 2 samples, and Salmonella paratyphi CO = 3 samples. This type of research is a descriptive study that aims to analyze the results of the Widal Slide Test with the agglutination method in the Sundari General Hospital Laboratory, Medan. Of the 15 samples analyzed, the results of the Widal Slide Test were obtained for 33% of typhoid fever patients with agglutination and 67% of those without agglutination. The results were Salmonella typhi O = 4 samples, Salmonella typhi H = 1 sample, Salmonella paratyphi AO = 1 sample, Salmonella paratyphi BO = 2 samples, and Salmonella paratyphi CO = 3 samples.